2021
DOI: 10.3390/plants10102207
|View full text |Cite
|
Sign up to set email alerts
|

Change in H+ Transport across Thylakoid Membrane as Potential Mechanism of 14.3 Hz Magnetic Field Impact on Photosynthetic Light Reactions in Seedlings of Wheat (Triticum aestivum L.)

Abstract: Natural and artificial extremely low-frequency magnetic fields (ELFMFs) are important factors influencing physiological processes in living organisms including terrestrial plants. Earlier, it was experimentally shown that short-term and long-term treatments by ELFMFs with Schumann resonance frequencies (7.8, 14.3, and 20.8 Hz) influenced parameters of photosynthetic light reactions in wheat leaves. The current work is devoted to an analysis of potential ways of this ELFMF influence on the light reactions. Only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 77 publications
(183 reference statements)
2
4
0
Order By: Relevance
“…In our experiments, the MF did not affect the main indicators of the light-dependent stage of photosynthesis (Fv/Fm, Φ PSII , NPQ) when plants were grown in the absence of the stressor (groups “Control” and “MF”) ( Figure 4 ). This agrees with the data from the literature, according to which the activity of photosynthesis, as well as the morphometric parameters, does not change under the action of MFs with characteristics similar to ours [ 13 , 14 , 18 ]. At the same time, some studies have demonstrated the stimulating effect of the MF [ 2 , 8 , 9 , 10 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our experiments, the MF did not affect the main indicators of the light-dependent stage of photosynthesis (Fv/Fm, Φ PSII , NPQ) when plants were grown in the absence of the stressor (groups “Control” and “MF”) ( Figure 4 ). This agrees with the data from the literature, according to which the activity of photosynthesis, as well as the morphometric parameters, does not change under the action of MFs with characteristics similar to ours [ 13 , 14 , 18 ]. At the same time, some studies have demonstrated the stimulating effect of the MF [ 2 , 8 , 9 , 10 ].…”
Section: Discussionsupporting
confidence: 93%
“…At the same time, some studies have demonstrated the stimulating effect of the MF [ 2 , 8 , 9 , 10 ]. It has been shown that the MF influence is realized due to both changes in the number of structural components (photosynthetic pigments and individual photosynthetic enzymes, for example, Rubisco) and changes in the activity of the light-dependent reactions associated with the electron transport chain and changes in the rate of absorption of CO 2 [ 2 , 8 , 10 , 13 , 14 , 19 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some works showed that low strength low-frequency MF is capable of affecting photosynthetic processes in plants. 5 , 7 , 9 , 10 In our recent works, the effect of the field with analogous parameters was shown to be capable of increasing efficiency 12 and progression rate 11 of light reactions of photosynthesis in wheat seedlings. The field-induced enhancement of proton leakage across the thylakoid membrane, as well as the stimulation of an additional H + flux caused by an increase in Ca 2+ concentration due to the activation of the H + /Ca 2+ antiporter, were suggested as key mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters of MF acting on the plants were chosen based on the most pronounced effects found during the analysis of frequency-amplitude dependency of the effect ELFMFs on photosynthesis, performed earlier. 11 , 12
Figure 1. Effect of extremely low-frequency MF on the parameters of light-induced electric reaction of the wheat seedlings.
…”
Section: Methodsmentioning
confidence: 99%